Interpretation of nevirapine concentration from immunochromatographic strip test using support vector regression - Sumonphan E. (2014)
Follow-up of human immunodeficiency virus (HIV) patients treated with nevirapine (NVP) is a necessary process to evaluate the drug resistance and the HIV mutation. t is also usually tested by immunochromatographic (IC) strip test. However, it is difficult to estimate the amount of drug the patient gets by visually inspection of color. This study proposes the method of evaluating the drug concentration from IC strip test using Support Vector Regression (SVR). The results from the proposed method are compared with the result obtained from multilayer perceptrons (MLP). It is found that SVR produce higher accuracy than MLP. © 2008 IEEE.